Link adaptation in mobile communications - Entrambasaguas-Muñoz, José Tomás (My University, 2018)
The different link adaptation techniques used mainly in mobile communication systems are described. Adaptation of modulation. Adaptation of channel coding rate. Joint adaptive modulation and coding (AMC). Performance of AMC and comparison with systems without adaptation. Adaptation of the MIMO scheme. Hybrid retransmission techniques (H-ARQ) Se describen las diferentes técnicas de adaptación de enlace empleadas principalmente en los sistemas de comunicaciones móviles. Modulación y codificación adaptativas (AMC). Prestaciones y comparación con sistemas sin adaptación Adaptación del esquema MIMO. Retrasmisión híbrida (H-ARQ).
Keywords: Comunicaciones digitales; Digital communications; Adaptive modulation; Adaptive modulation and coding, AMC; MIMO adaptation; Hybrid ARQ, H-ARQ; Mobile communications